Technology acceptance model theory on intention to use e-recruitment - Azzatillah Azzatillah; Lifatin Nada; Dean Seshar Rahmadina; Chairunnisa Chairunnisa; Dhelvianti Azni Savira (Universitas Ahmad Dahlan, 2024)
Currently, e-recruitment activities are human resource digitalization activities that not only change the perspective of job seekers about finding and applying for jobs but also change the way organizations attract new candidates to job positions. This study examines and analyzes the intention to use e-recruitment using the development of the theory of technology acceptance model 2. The quantitative method is the research method used in this study. The sample collection used purposive random sampling through an online questionnaire to obtain a sample of 177 respondents. The analysis in this study uses a variant-based structural equation model with partial least squares. The analysis results indirectly show that someone with a subjective norm will have a higher perceived usefulness of e-recruitment, affecting the higher intention to use e-recruitment. This also happens to someone who has a perceived ease of use of e-recruitment, which will increase the perceived usefulness of e-recruitment, increasing the intention to use e-recruitment. Subjective norm will directly affect someone's intention to use and perceived usefulness of e-recruitment; perceived usefulness will affect intention to use e-recruitment; and perceived ease of use will influence perceived usefulness and intention to use e-recruitment.